Living with low environmental complexity increases fear indicators in Nile tilapia - Tatemoto, P.; Valença-Silva, G. [UNESP]; Queiroz, Mariana R.; Broom, Donald M. (Elsevier, 2021)
Animals are often kept in conditions with low environmental complexity and for long periods in barren artificial environments. This has been shown to lead to poor welfare in many species of animals. We assessed the emotional responses of Nile tilapia, Oreochromis niloticus L., maintained for different intervals in a barren or enriched environment. Four groups of fish were tested individually for emotionality by inserting a novel object in the glass aquarium to assess behavioural responses, such as indicators of fear and exploratory behaviours. Fish kept for 7 weeks in barren environments showed behavioural indicators of fear in response to the novel object test performed in each isolated fish. Enriched environment increased the time investigating a novel object. The reduced time spent performing behaviours that indicate fear during the novel object test in fish kept in an enriched environment shows that the responses were a consequence of lack of stimuli, not necessarily social isolation. More complex environments improve the affective states and welfare of tilapia.
Keywords: animal welfare; barren environment; emotional response; enrichment; fear; tilapia